Blizzard! : the storm that changed America - Murphy, Jim (New York : Scholastic Inc., 2000)
Presents a history based on personal accounts and newspaper articles of the massive snowstorm that hit the Northeast in 1888, focusing on the events in New York City.
Includes Bibliographical references and index.
Keywords: New York (N.Y.) -- History -- 1865-1898 -- Juvenile literature; Blizzards -- New York (state) -- History 19th century -- Juvenile literature